Modeling of interactions between xenobiotics and cytochrome P450 (CYP) enzymes - Raunio, Hannu; Kuusisto, Mira; Juvonen, Risto O.; Pentikäinen, Olli T. (Frontiers in Pharmacology, 2015)
The adverse effects to humans and environment of only few chemicals are well known. Absorption, distribution, metabolism and excretion (ADME) are the steps of pharmaco/toxicokinetics that determine the internal dose of chemicals to which the organism is exposed. Of all the xenobiotic-metabolizing enzymes, the cytochrome P450 (CYP) enzymes are the most important due to their abundance and versatility. Reactions catalyzed by CYPs usually turn xenobiotics to harmless and excretable metabolites, but sometimes an innocuous xenobiotic is transformed into a toxic metabolite. Data on ADME and toxicity (ADMET) properties of compounds are increasingly generated using in vitro and modeling (in silico) tools. Both physics-based and empirical modeling approaches are used. Numerous ligand-based and target-based as well as combined modeling methods have been employed to evaluate determinants of CYP ligand binding as well as predicting sites of metabolism and inhibition characteristics of test molecules. In silico prediction of CYP-ligand interactions have made crucial contributions in understanding 1) determinants of CYP ligand binding recognition and affinity; 2) prediction of likely metabolites from substrates; 3) prediction of inhibitors and their inhibition potency. Truly predictive models of toxic outcomes cannot be created without incorporating metabolic characteristics; in silico methods help producing such information and filling gaps in experimentally derived data. Currently modeling methods are not mature enough to replace standard in vitro and in vivo approaches, but they are already used as an important component in risk assessment of drugs and other chemicals.